About the validity of Alois Riegl's The Modern Cult of Monuments. Issue 3 (2nd September 2022) - Burgos Vargas, Camila; Mora Alonso-Muñoyerro, S.
ABSTRACT: The extensive literature about heritage values makes it difficult to find a typology that can be used as a standard tool for value assessment. Instead of proposing a new typology, this article takes a step back to examine the value typology defined by Alois Riegl in The Modern Cult of Monuments. Its Character and its Origin (1903) and, analysing it along with a sample of other typologies, to find out if it is still useful today and how it can be adapted to the changes in Heritage Conservation in Europe during the circa 120 years since its creation. The result is an updated value typology that could be applied to historical and recent heritage.